Effect of kaolinites modified with Zr and transition metals on the pyrolysis behaviors of low-rank coal and its model compound. (April 2021) - Zhong, Mei; Zou, Da; Xu, Yuebing; Jin, Lijun; Pan, Yue
Abstract: Acid treated kaolinites (KA) were successively loaded with Zr and Fe, Ni or Co component to control the product distribution and upgrade the tar quality in coal pyrolysis. The structure of the resultant catalysts was characterized and their catalytic performance in the pyrolysis of demineralized low-rank coal and benzyl phenyl ether (BPE), a model compound containing Cal -O bridge bond, were investigated. Results show that the introducing of Zr into the KA can enlarge the hysteresis loop due to the stacking of ZrO2 particles. The acidities, especially the strong ones, increase as the Zr content is below 8 wt% (KA-8Z). When adding Fe, Ni or Co metals into the KA-8Z, the number of Brønsted acid sites obviously decreases, but Lewis acid sites increase. The maximum BPE conversion of 94.0% occurs for the KA-8Z, further metal-loaded sample promotes the cleavage of Cal -O bond in BPE and the formation of active H radicals from CH3 OH, leading to the increase of BPE conversion. Besides, remarkable enhancement of target monomeric aromatics is observed for the Fe, Ni and Co-loaded samples. Compared with the pyrolysis without catalyst, the tar yield as well as pitch content decrease over the KA-8Z and its metal-modified catalysts. Wherein, Ni-KA-8Z has the highest activity for tar upgrading, leading to the largest increase in the contents of light oil and phenol oil. In-situ pyrolysis by time-of-flight mass spectrometry reveals the enhanced dissociation of weak covalent bonds linked in the coal skeleton over the KA-8Z and Fe, Ni and Co-modified catalysts, resulting in a decrease in the peak temperature for product release. A marked increase in phenols and diphenols confirms a promoted dissociation of ether bond in coal. Highlights: Introducing of Zr and metals into the KA can regulate the acidities of the catalysts. Zr and metal-modified kaolinites promote the cleavage of C –O bond in BPE. Zr and metal-modified samples decrease pitch content and increase light tar fraction. Py-TOF-PIMS results confirm a promoted dissociation of ether bond in coal.